A journey through modern foundations: Re-imagining modernity in the work of Photolanguage. (1st June 2018) - Wilson, Robin
This article reflects on the use of arts-based research methods to engage with a regional history of modern architecture and urbanism. Moving between archival sources and the remaining physical sites in East Sussex, the art practice Photolanguage documented and reimagined the modernist legacy in this region of southern England. Through photography, the gathering of found objects and notation, we construct 'new' narratives of place, working across, or in between the official, or dominant, narratives of local history. This reflection back on the production of work for the exhibition East Sussex Modern (2016) focuses on our adoption of the modern 'sunken garden' as a recurrent, topographic theme and our exploration and projective appropriation of found ruins as alternative examples of this official, municipal typology of public space.